Comparison Of Field And Laboratory Short Term Aging Of Asphalt Binder And Mixture - Omranian, Seyed Reza (2013)
Aging is a complex physico-chemical phenomenon that influences asphalt binder and mixture rheological properties causing deterioration in asphalt mixture performance. To enhance the pavement performance, characterisation of the asphalt binder and asphalt mixture due to short term aging is required. This study is divided into two phases. The first phase evaluated and characterized the asphalt binder rheological properties before and after short term aging. The Rolling Thin Film Oven (RTFO), Dynamic Shear Rheometer (DSR), Rotational Viscometer (RV), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD) tests were used to evaluate behaviour of virgin, artificially aged and extracted asphalt binders. The second phase dwelt upon the behaviour of dense asphalt mixture produced by Kuad Quarry Sdn. Bhd, after subjected to short term aging. The indirect tensile strength, dynamic creep, resilient modulus and diametral fatigue tests were carried out to assess and determine the effects of short term aging on field, plant and artificially aged asphalt mixtures. All the binder and mixture tests results were compared to evaluate and determine the short term aging effect during production. The results showed that the aging increases the viscosity and hardening of the binder and mixture. The binder rheological test results indicated that aging increased the complex modulus, rutting factor, viscosity and torque but decreased the phase angle. The FTIR results indicated that aging only affected the binder carbonyl and sulfoxides bands. From the XRD results aging affect the range 2θ between 30° and 90° by decreasing the binder pattern intensity.